Síntese e modificação de estruturas metal orgânicas utilizadas como catalisadores na hidroxilação do fenol - Santos, Danilo Fernandes dos (2025)
Phenol plays a crucial role in the chemical industry, serving as a raw material for various products. Among the several transformation routes of phenol, hydroxylation stands out, enabling the production of dihydroxybenzenes, mainly catechol and hydroquinone, high-value-added products with diverse applications, such as in the production of pharmaceuticals, pesticides, spices, paints, dyes, rubbers, fine chemicals, among others. The high demand for these compounds stimulates research related to their production through direct hydroxylation processes with heterogeneous catalysts, since they are traditionally produced by sulfonation and chlorination processes via homogeneous catalysis, generating liquid residues from the process. This work aimed to synthesize and modify Metal-Organic Frameworks (MOFs), specifically NH2-MIL-101(Fe), and evaluate their catalytic behavior in a direct hydroxylation reaction of phenol to form higher value-added products, mainly dihydroxybenzenes. In this context, the work carried out consisted of analyzing heterogeneous catalysis as an advantageous alternative to traditional processes. Furthermore, modulators (Oxalic Acid) were added to the structure to enhance the hydroxylation results. It was observed, through various analytical characterization techniques, that the modulator was added to the NH2-MIL-101(Fe) structure as expected. In the hydroxylation tests, 83.5% phenol conversion was observed when performed at a temperature of 25 ºC, 7% catalyst, and a H2O2/Phenol molar ratio of 2. The chromatograms identified the formation of only two reaction products, catechol and hydroquinone.